Dynamic Characterization of the Joints in a Beam Structure by Using Spectral Element Method - Usik Lee (Shock and Vibration)
A frequency-domain approach is introduced to identify the dynamic characteristics of the mechanical joints within a one-dimensional structure. In this paper, a cantilevered beam structure with a bolt-joint is considered as an illustrative problem. The beam structure consists of two Timoshenko-beams connected to each other by a bolted joint. The bolt-joint is represented by the equivalent joint model with four parameters, and the four parameters are determined from the experimentally measured frequency response functions (FRF). To improve the accuracy of the identified bolt-joint parameters, the spectral element models are used for two Timoshenko-beams. Experiments are conducted for the cantilevered beam structure and the four bolt-joint parameters determined from the measured FRF. The spectral analysis is conducted to predict the dynamic responses of the beam structure by using the spectral bolt-joint element that is determined from the identified bolt-joint parameters. It is found that the analytical predictions are in general quite in good agreement with the experimentally measured dynamic responses.